Generalized Almost Distributive Fuzzy Lattices - Berhanu Assaye Alaba; Yohannes Gedamu Wondifraw (LPPM Institut Teknologi Sepuluh Nopember, 2017)
In this paper we introduce the concept of a Generalized almost distributive fuzzy lattices (GADFLs) as a generalization of an Almost distributive fuzzy lattices(ADFLs). Again, we also show that a necessary and sufficient conditions for a GADFLs to become a distributive fuzzy lattices and a GADFLs to become an ADFLs